Case report: The intrauterine suture surgery—an original method in the treatment of old uterine false passage - Xiaolei Song; Re Na; Nianghai Peng; Wenming Cao; Yan Ke; Ping Liu; Chunlin Chen (Frontiers in Surgery, 2023)
ObjectiveTo introduce an effective approach using the hysteroscopy system for patients with old uterine false passage after a failed conservative treatment.Materials and methodsThis study presents the case of a 34-year-old woman who was treated in the Department of Gynecology of Shenzhen Integrated Traditional Chinese and Western Medicine Hospital in 2018 with the complaint of “menstrual volumereduction for 2 years after abortion.” A hysteroscopy was performed to make a clear diagnosis: (1) uterine cavity adhesion and (2) old uterine false passage. After the separation of adhesions, the patient was treated with estradiol and progesterone in sequence (estradiol valerate 3 mg, b.i.d., oral for 21 days; and dydrogesterone tablets 10 mg, b.i.d., oral for the second half of the cycle) for 3 months. After the review of the hysteroscopy results, it was found that there was no improvement in the old false passage; therefore, a suture and knotting surgery under hysteroscopy was performed to treat the old false passage in the uterus within 10 min, and the intraoperative blood loss was 2 ml. The patient was discharged 24 h postoperatively without any adverse perioperative complications.ResultsTwo months after the operation, the review of the hysteroscopy results showed that the old false passage in the uterus disappeared. After the 6-month follow-up, the menstrual volume increased compared with the previous one, close to the normal menstrual volume, and the patient experienced no pain and menstrual discomfort. The patient was lost to follow-up and was contacted again in 2022. It was found out that in 2019, she was pregnant with a baby boy who is now 3 years old and healthy.ConclusionThe intrauterine suture surgery presents a clear visual ﬁeld to old uterine false passage after a failed conservative treatment. In patients with old uterine false passage suffering from reduced fertility, the intrauterine suture surgery can be a minimally invasive and effective alternative if the conservative treatment for old uterine false passage failed.